Powers that be - McCaffrey, Anne (Ballantine Books, 1993)
Strange things were happening on the icy planet called Petaybee. Unauthorized genetically engineered species had been spotted, while some people were simply disappearing. None of the locals were talking to the company, so the company sent disabled combat veteran Yanaba Maddock to spy. But a strange thing happened. With her relocation to the arctic planet came a return of Yana's health and strength. And the more she got to know the people of Petaybee, the more determined she became to protect her new home....